INFORMATIONAL AND ORGANIZATIONAL AND LEGAL BASIS FOR PROTECTING YOUNG PEOPLE FROM DESTRUCTIVE IDEAS - Abdumalikov Abdulatif Abidjanovich; Kadyrov is the son of Shokhrukhbek Musajon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, information in the world is of great importance in international and inter-state relations.